The Role of Alpha Blocker Drugs in Reducing Double J Stent Related Symptoms - Memon, Waqar Ahmed; Khowaja, Ali Haider; Khalid, Salman El; ., Asadullah; Saulat, Sherjeel; Sheikh, Jahanzeb; Abid, Khadijah (Pakistan Armed Forces Medical Journal, 2024)
Objective: To determine the effect of alpha blocker drugs on reduction of Double J Stent related symptoms. Study Design: Quasi-experimental study. Place and Duration of Study: Department of Urology, The Kidney Centre, Post Graduate Training Institute, Karachi Pakistan, from May 2014 to Nov 2019. Methodology: Total 92 patients who had unilateral stent, inserted retrograde or antegrade, were studied. On 7th postoperative day double J stent related symptoms were documented on Ureteral Stent Symptom Questionnaire and alpha-blocker was started if score is >10. After 4 weeks, data was again collected to assess mean change in Ureteral Stent Symptom Questionnaire score. Results: Of 92 patients, pre-treatment mean Ureteral Stent Symptom Questionnaire score was 38.36±16.07 and post treatment was 14.87±8.62. Mean difference between pre and post Ureteral Stent Symptom Questionnaire score was found significant (p<0.05). Conclusion: Administration of Tamsulosin has a positive effect on stent related urinary symptoms and quality of life.